Prevalence and clinical characteristics of refractoriness to optimal proton pump inhibitor therapy in non‐erosive reflux disease. Issue 10 (7th October 2018) - Ribolsi, Mentore; Cicala, Michele; Zentilin, Patrizia; Neri, Matteo; Mauro, Aurelio; Efthymakis, Konstantinos; Petitti, Tommasangelo; Savarino, Vincenzo; Penagini, Roberto
Summary: Background: The real size of the gastro‐oesophageal reflux disease (GERD) population not responding to proton pump inhibitor (PPI) therapy has still not been fully elucidated. Causes of PPI refractoriness include incorrect diagnosis and lack of adherence to therapy, in terms of incorrect dosage and timing. Aims: To evaluate the prevalence of refractoriness to optimal PPI therapy and the contribution of non‐erosive reflux disease (NERD), reflux hypersensitivity, and functional heartburn, to PPI refractoriness. The association of functional GI symptoms in non‐responders was evaluated. Methods: Frequency and severity of GERD symptoms (heartburn, regurgitation, chest pain), dysphagia, belching, epigastric pain, postprandial distress, irritable bowel syndrome (IBS), globus, and ear nose and throat (ENT) symptoms were evaluated in patients previously classified as non‐responders. Patients with at least one of the oesophageal symptoms with a frequency ≥3 /week were treated with esomeprazole 40 mg once daily for 8 weeks and then re‐evaluated. Non‐responders (patients with oesophageal symptoms ≥3 times per week) underwent 24 hour multichannel intraluminal impedance‐pH monitoring. Results: Of 573 consecutive patients, 92 with oesophageal symptoms and classified as PPI‐refractory underwent the esomeprazole trial; 60 did not respond. IBS, epigastric pain, and post‐prandial distress episodes were associated with a poor response on multivariate analysis. NERD, reflux hypersensitivity, and functional heartburn patients constituted 32%, 42%, and 26%, respectively of the PPI‐refractory group. Conclusions: True refractoriness in patients with GERD symptoms attending a secondary care setting is lower than previously reported. Following a careful history and optimal PPI dosing, the rate of refractoriness was 20%. True NERD constitutes only a third of the PPI‐refractory group.